ILAE Neuroimaging Task Force Highlight: harnessing optimized imaging protocols for drug‐resistant childhood epilepsy. Issue 5 (16th November 2021) - Larivière, Sara; Federico, Paolo; Chinvarun, Yotin; Jackson, Graeme; Morgan, Victoria; Rampp, Stefan; Vaudano, Anna Elisabetta; Wang, Irene; Cendes, Fernando; Boelman, Cyrus G.; Bernasconi, Andrea; Bernasconi, Neda; et al.
Abstract: The ILAE Neuroimaging Task Force aims to publish educational case reports highlighting basic aspects related to neuroimaging in epilepsy consistent with the educational mission of the ILAE. Previous quantitative MRI studies have established important imaging markers of epilepsy‐related pathology, including features sensitive to hippocampal cell loss and reactive astrogliosis. Here, we review the case of a female with pediatric drug‐resistant epilepsy. Throughout her course of treatment, she had seven MRI investigations at several centers; the first three did not follow optimized epilepsy imaging protocols whereas the remaining four adhered to HARNESS‐MRI protocols (har monized n euroimaging of e pilepsy s tructural s equences). Visual inspection of a set of HARNESS‐MR images revealed conspicuous left hippocampal hyperintensity which may have been initially overlooked on non‐optimized MR images. Quantitative analysis of these multimodal imaging data along hippocampal subfields provided clear evidence of hippocampal sclerosis, with increased atrophy, increased mean diffusivity, increased T2‐FLAIR signal, and lower qT1 values observed in the anterior portions of the left, compared to the right hippocampus. The patient underwent a left anterior temporal lobectomy with amygdalohippocampectomy at age 16 years. Histopathology of the resected specimen also confirmed hippocampal sclerosis with widespread gliosis and focal neuronal loss in the hippocampal subfields overlapping with regions of multimodal quantitative alterations. The patient remains seizure‐free one year after surgery. Collectively, this case highlights the need for optimized data acquisition protocols early in the treatment of epilepsy and supports quantitative analysis of MRI contrasts to enhance personalized diagnosis and prognosis of drug‐resistant patients with epilepsy.